Resolving the kinematics of the discs around Galactic B[e] supergiants. Issue 1 (4th July 2018) - Maravelias, G; Kraus, M; Cidale, L S; Borges Fernandes, M; Arias, M L; Curé, M; Vasilopoulos, G
ABSTRACT: B[e] supergiants are luminous evolved massive stars. The mass-loss during this phase creates a complex circumstellar environment with atomic, molecular, and dusty regions usually found in rings or disc-like structures. For a better comprehension of the mechanisms behind the formation of these rings, detailed knowledge about their structure and dynamics is essential. To address that, we obtained high-resolution optical and near-infrared (near-IR) spectra for eight selected Galactic B[e] supergiants, for which CO emission has been detected. Assuming Keplerian rotation for the disc, we combine the kinematics obtained from the CO bands in the near-IR with those obtained by fitting the forbidden emission [O i ] λ5577, [O i ] λλ6300, 6363, and [Ca ii ] λλ7291, 7323 lines in the optical to probe the disc structure. We find that the emission originates from multiple ring structures around all B[e] supergiants, with each one of them displaying a unique combination of rings regardless of whether the object is part of a binary system. The confirmed binaries display spectroscopic variations of their line intensities and profiles as well as photometric variability, whereas the ring structures around the single stars are stable.